Perancangan Website Pemesanan Event Organizer Ulang Tahun CV. Alinea Birthday Club - khodijah, zaitun; Astuti, Bela; Wicaksana, Muhamad Dwi Cahya; Firmansyah, Muhamad Rehan; Assobry, Muhammad Habib; Zidan, Zidan; Ramadani, Ahmad; Endraswari, Putri Mentari (Journal Software, Hardware and Information Technology, 2025)
In the current era of globalization, technology and communication are developing rapidly so that everything is practical and fast. Modern technology offers an online ordering system. However, there are still event organizers, especially in the Pangkalpinang area, whose systems are still manual. In general, consumers have to make a date first to order an event organizer. Based on the discussion above, the aim of the author's research is to create an event organizer booking system using the Website-Based Waterfall Method. This is so that it can be accessed easily using a smartphone. Research data was collected by conducting interviews with event organizers and direct observation at the target location. This system design has 2 actors, namely the buyer and the admin. Based on the results of research and analysis carried out by the author, this waterfall development model provides a structured system framework for designing the development of an event organizer booking system